Effect of a heterogeneous network on glass transition dynamics and solvent crack behavior of epoxy resins. Issue 32 (4th August 2020) - Aoki, Mika; Shundo, Atsuomi; Yamamoto, Satoru; Tanaka, Keiji
Abstract : Network structure in an epoxy resin, which became more heterogeneous with increasing pre-curing temperature, affected the glass transition dynamics and solvent crack behavior. Abstract : In general, it has been widely accepted that the physical properties of an epoxy resin are strongly dependent on how it is prepared. However, a clear understanding of the mechanisms of the relationship at a molecular level has yet to be achieved. We here studied the glass transition dynamics and fracture behavior of four epoxy resins, which were pre-cured at different temperatures and well cured under the same conditions. Fourier-transform infrared spectroscopy revealed that the reaction kinetics for an epoxy-amine mixture were strongly dependent on the pre-curing temperature. The glass transition temperature of epoxy resins with the same cross-linking density was dependent on the pre-curing temperature. Dielectric relaxation spectroscopy and dynamic mechanical analysis revealed that the fragility index of the epoxy resin decreased with increasing pre-curing temperature, indicating that the network structure formed in it became more heterogeneous with increasing pre-curing temperature. Once the epoxy resin was immersed in a good solvent, it was partly swollen and was then macroscopically fractured. The fracture was initiated by the crack generation in an un-swollen region of the resin due to the stress induced upon swelling. The immersion time required to reach the fracture decreased as the extent of the heterogeneity increased. The knowledge here obtained should be useful for understanding and controlling fracture toughness of epoxy resins, leading to the furtherance of their functionalization.